ANALISIS DATA HIDROLOGI SUNGAI AIR BENGKULU MENGGUNAKAN METODE STATISTIK - Gunawan, Gusta (Inersia: Jurnal Teknik Sipil, 2017)
Bengkulu municipality as a constituent element of the Air Bengkulu watershed with 51,500 of hectares area bypassed by the stream of Air Bengkulu River which empties into the Teluk Segara District, municipal of Bengkulu. Air Bengkulu River suffered flood at least twice a year of frequency as result of the increase in water discharge (Q) in the rainy season. The purpose of this research is to calculate the amount of peak river discharge of Air Bengkulu and mappingthe distribution of inundation water that may occur in the city of Bengkulu. Analysis of the mean daily maximum rainfall area was conducted by Thiessen Polygon using 15 last years of rainfall datas. Calculation of peak discharge using rational methods for different return period plans Analysis of Rainfall of flood modeling simulation is done by using HEC-RAS 4.1.0 and flood inundation mapping is done by using Hec-GeoRAS 4.3.1 flood modeling. The result of rainfall plan calculations was qualified by Gumbel type 1 method. The results of the Air Bengkulu river peak discharge quantify for return period 5, 10, 25, 50 and 100 years respectively 339.66 m3/sec; 470.38m3/sec; 520.59m3/sec; 557.83m3/sec; 594.79m3/sec; 631.62m3/sec. Results of generated mapping showed the areas affected by flood inundation in Bengkulu City namely Pasar Bengkulu village, Kampung Klawi, Rawa Makmur, Suka Merindu, Tanjung Agung,Tanjung Jaya, and Semarang. The depth value of inundation mapping for every affected village of floodwaters are vary, but in the range of 0 - 110 cm.